2020
DOI: 10.1111/1759-7714.13720
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of survival among Japanese patients receiving first‐line chemoimmunotherapy for advanced non‐small cell lung cancer

Abstract: Background: First-line chemoimmunotherapy (CIT) has improved overall survival (OS) and progression-free survival (PFS) outcomes among patients with non-small cell lung cancer (NSCLC). The immunological and nutritional statuses of patients fluctuate during treatment using immune checkpoint inhibitors, and are closely related to treatment outcomes. However, it is unclear whether these markers are significant in patients who are receiving CIT. Methods: This retrospective single-center study evaluated 34 consecuti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 48 publications
0
21
1
Order By: Relevance
“…Antitumor neovascularization is an important aspect of targeted therapy, but the evaluation standard for tumor efficacy is mainly the evaluation to chemotherapy drugs' efficacy (17)(18)(19). Antiangiogenic drugs act on the blood vessels of tumors, and most of them cannot quickly shrink tumors, because tumorous volume change often comes later than blood supply inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Antitumor neovascularization is an important aspect of targeted therapy, but the evaluation standard for tumor efficacy is mainly the evaluation to chemotherapy drugs' efficacy (17)(18)(19). Antiangiogenic drugs act on the blood vessels of tumors, and most of them cannot quickly shrink tumors, because tumorous volume change often comes later than blood supply inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Five publications showed that PNI was an independent predictor of unfavorable PFS in cancer patients with immunotherapy (18,19,26,27,34), whereas five cohort studies detected no significant relationship between PNI and PFS (20,28,30,31,33). The combined analysis of ten studies that enrolled 1,282 participants showed that a higher PNI level was associated with worse PFS (pHR = 1.61, 95% CI = 1.37-1.88, Figure 3).…”
Section: Correlation Between Pretreatment Prognostic Nutritional Inde...mentioning
confidence: 98%
“…Five observational studies reported that PNI was an independent indicator for a shortened OS in cancer patients with immunotherapy (18,19,(26)(27)(28), while PNI was not considered as a prognostic factor for OS in seven studies (20,(29)(30)(31)(32)(33)(34). Pooled analysis of all selected publications revealed that the PNI values higher than the cutoff value predicted a poor OS (pHR = 2.24, 95% CI = 1.57-3.20, Figure 2) in advanced cancer patients treated with immune checkpoint inhibitors.…”
Section: Correlation Between Pretreatment Prognostic Nutritional Inde...mentioning
confidence: 99%
“…There was no significant association between B-GPS and response to chemotherapy. Studies of the prognostic role of GPS in cancer comprise more than 70 000 patients, [7][8][9] but only a few have looked at the impact of GPS measured during or after treatment: Three small studies (n = 24-64) reported that elevated GPS measured 3 to 6 weeks after initiation of immune checkpoint inhibitor therapy was associated with poor survival in advanced NSCLC 30,31 and renal cell carcinoma. 32 Others have found that elevated GPS after initiation of palliative chemotherapy for colorectal cancer 33 and after surgery for localized NSCLC 34 and gastric cancer 15 was associated with poor prognosis.…”
Section: Discussionmentioning
confidence: 99%